The impact of competition for picking wild edible mushrooms and the opportunity cost for rural communities: the case of Castile and León (Spain) - Pablo de Frutos Madrazo; Joaquín Latorre Minguell; Pedro Antonio Martín-Cervantes; Fernando Martínez Peña (Frontiers in Sustainable Food Systems)
Picking wild edible mushrooms is a key activity both for rural as well as urban communities. Studies into the topic support the notion of the major socio-economic benefits, which increase both producer as well as consumer surplus. However, to date, no study has estimated picking harvests in the way this study does or what effects these might have on local communities with regard to other activities, both in terms of work and leisure time. This study explores both issues, taking as an indicator a variable used in conventional analysis in other sectors, yet which thus far has not been employed in wild edible mushroom picking: productivity value. The chosen study area is the autonomous community of Castile and León, a Spanish region with an important and long-running mycological tradition. Using the decision-making method between individuals’ leisure time and work time, the authors test the corresponding hypotheses. The results that emerge for the years analyzed (2013 and 2014) support the hypothesis of distorting/moderating effects related to the effects of picking yields on pickers’ income and their impact on the individual supply for labor function of pickers.